Dataset for CSAE Working Paper WPS/2008-09 - Quinn, S; Teal, F (University of Oxford, 2008)
Dataset for CSAE Working Paper WPS/2008-09: "Private sector development and income dynamics: A panel study of the Tanzanian labour market"